The estrogenic effect of genistein on vitellogenin synthesis in the mature male goldfish (Carassius auratus) - Elham Nezafatian; Vahid Zadmajid (بوم‌شناسی آبزیان, 2018)
In the present study, the effects of estrogenic genistein or 17β-estradiol (E2) was investigated on vitellogenin synthesis in mature male goldfish. Matures male goldfish received intraperitoneal injections of E2 (10 μg/g body weight), one of two genistein doses (5 μg/g body weight, G5, or 50 μg/g body weight, G50), or the injection vehicle every other day for 10 days during spermiation phase. Ten days after the first injection, blood was collected. The induction of VTG was determined in plasma of treated fish indirectly by measuring the Alkaline Phosphatase (ALP), 17β-estradiol and blood serum biochemical indicators (phosphorous, calcium and triglycerides). The regression analysis revealed positive and significant relationship between ALP concentration and levels of blood serum 17β-estradiol phosphorous, and triglycerides (P˂ 0.05).  However the correlation between ALP and calcium blood serume was not significant (P˃ 0.05). Our results suggest that high doses of genistein stimulates vitellogenin synthesis by increasing the levels of serum ALP. This was confirmed by positive and significant correlations among the concentrations of blood ALP and phosphorus, triglycerides and 17β-estradiol hormone.